Trabecular Bone Score and Osteoprotegerin as Useful Tools in the Assessment of Bone Deterioration in Acromegaly - Jawiarczyk-Przybyłowska, Aleksandra; Halupczok-Żyła, Jowita; Syrycka, Joanna; Zembska, Agnieszka; Kuliczkowska-Płaksej, Justyna; Bolanowski, Marek (Frontiers in Endocrinology, 2022)
Purpose: This study aimed to assess bone mineral density (BMD) and trabecular bone score (TBS) in 61 patients from the acromegaly group (AG) with regard to the activity of the disease in comparison to 42 patients - control group (CG). We also analyzed selected bone markers and their association with BMD and TBS. Materials and Methods: Lumbar spine and femoral neck BMD measurements were performed. TBS values were obtained. Serum concentrations of selected bone markers, including osteoprotegerin (OPG) were measured. Results: We revealed a difference of TBS values between the AG and CG as well as between the TCA (treatment-controlled acromegaly) vs CG and TCA+CA (cured acromegaly) vs CG. We did not observe any statistically significant difference in BMD. OPG had a lower concentration in the control group compared to acromegaly group. TBS correlated negatively with OPG in the AG (r=-0.31, p=0.01) and in the TCA+ CA group (r=-0.3, p=0.01). Conclusions: The acromegalic patients have altered bone microstructure as indicated by the decreased TBS regardless of the activity of the disease and BMD. OPG could be the marker of the destruction of the bone microstructure but further studies are needed.